The expanded public works programme as a tool for local economic development: policies,processes, mechanisms and institutional arrangements - Mogane, Maurice Charles (My University, 2006)
The re-admittance of South Africa into the community of nations brought opportunities and challenges. South Africa had to adapt and conform to the prevailing global economic architecture and adhere to neo-liberal principles prevailing at the time while at home it had to face a restructuring economy and worsening social conditions for a majority of its people: unemployment, housing and infrastructure backlogs. Policies and programmes where devised and adopted. The EPWP and local economic development programmes are just two of the many programmes meant to deal with unemployment, skills development, inequality and poverty. This report investigates the potential of the EPWP as a tool for local economic development by reviewing the theoretical underpinnings of public works and local economic development; and the intergovernmental relations and planning policies, processes, mechanisms, and institutional arrangements in place to enable the programmes’ implementation. Based on the investigation, findings and recommendations are made.
Student Number : 0407355G - MSc research report - School of Architecture and Planning - Faculty of Engineering and the Built Environment
Keywords: expanded public works programme; local economic development; inter-governmental relations; processes and policies